Electrophoretic‐deposited HAP nano‐layer as a QCM‐D sensor coating: effects of suspension concentration and electric‐field strength. Issue 3 (17th September 2018) - Zheng, Liang; Gong, Wei; Tang, Yue; Ma, Genlei; Zheng, Jing; Chen, Shi‐zhe; Li, Wei‐hua
Abstract : This study investigates the fabrication of hydroxyapatite (HAP) nano‐coating on a gold–quartz crystal sensor used for quartz crystal microbalance with dissipation (QCM‐D) measurement using an electrophoretic deposition technique. Surface morphology and thickness of the HAP coating are examined via scanning electron microscopy and nano‐indention testing. Its repeatability is verified via QCM‐D testing. Results show that electrophoretic deposition with ultrasonic treatment is feasible and cost‐effective for fabricating nano‐thick HAP coatings on a QCM‐D gold–quartz crystal sensor surface. Both suspension concentration and electric‐field strength influence the compactness of HAP coatings. There exists a non‐linear relationship between HAP coating compactness and the suspension concentration/electric‐field strength. When the HAP suspension concentration is 30 g/l and the applied electric‐field strength is 150 V/cm, the HAP coating on the QCM‐D gold–quartz crystal sensor surface is uniform and compact with a thickness of 35 nm and is tightly bonded to the sensor surface. The obtained HAP‐coated sensor is thus suitable for QCM‐D measurement.